Early Excision and Grafting in Burns: An Experience in a Tertiary Care Industrial Hospital of Eastern India - Prasenjit Goswami; Seelora Sahu; Pankaj Singodia; Manjeet Kumar; Tukulu Tudu; Abinash Kumar; Pankaj Kumar Sinha (Indian Journal of Plastic Surgery)
Introduction To compare the burn patients undergoing early excision and grafting (within 7 days of burn injury) with the patients undergoing late surgeries (more than 7 days after burn injury) to see if there was any difference in surgical and outcome parameters including length of stay, expenditure, and overall outcome of the patients. Material and Methods A retrospective analysis of the data collected from the burn care unit records over a period of one year was done. Fifty-eight patients who matched with our inclusion criteria were divided into two groups. An early excision group who underwent surgery within 7 days of sustaining burn injury (n = 24) and a late excision group who underwent excision and grafting/debridement after 7 days of sustaining burn (n = 34). Data recorded included demographic variables like age, sex, percentage total body surface area (TBSA) burn; nature of burn; date of sustaining burn; date of admission to the burn care unit; and treatment and outcome parameters like date of surgery, days from burn injury to first surgery, number of surgeries, type of surgery, percentage of TBSA resurfaced with skin graft, blood products used, length of stay, outcome, and total expenditure incurred by patients. Results There was no statistically significant difference in the number of surgeries done, the units of packed cell used, and the number of fresh frozen plasma (FFP) used between the early excision group and the late excision group. The length of stay was significantly low in the early excision group as compared with the late excision group. The expenditure incurred in the treatment of the early excision group was significantly lower than the cost of treatment of the late excision group. Conclusion Early excision and grafting in burn cases reduces the length of the stay of burn patients and, in turn, reduces the cost of treatment. However, having a dedicated burn care unit is important for the hospitals and both public and private hospitals should make a move in that direction.